PERAN PERUSAHAAN UMAT DALAM KOMPETISI GLOBAL - Sofyan S Harahap (Media Riset Bisnis & Manajemen, 2002)
Inline with the development of new states and their economy, the Muslimowned companies are emerging.  Sum of the companies are listed in the Emerging Market 200 of Business Week.  This new phenomenon are discussed and the composition and characteristics of those companies are analyzed.  These companies are not necessary being operated in syariah rudes.  The grouping is only based on what country are the companies originated.  The companies may not belong to Muslim investors or its operating may not comply with sharia rules.  The paper is a first step to discover and to map the road and the power of Muslim emerging Economy.